2019
DOI: 10.1016/j.jallcom.2018.08.199
|View full text |Cite
|
Sign up to set email alerts
|

The stability and physical properties of the tetragonal phase of bulk CuMnAs antiferromagnet

Abstract: The effect of Cu substitution on the stability of the CuMnAs tetragonal phase was studied both experimentally and by ab initio calculations. Polycrystalline samples with various compositions Cu1+xMn1-xAs (x = 0-0.5) were synthetized. The tetragonal phase of CuMnAs is found to be stabilized by substituting Mn by Cu in the amount of x ~ 0.1 or higher. This observation is supported by ab initio calculations of the total energy of the tetragonal and orthorhombic phases; with increasing Cu content the tetragonal ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…On the experimental side, we note that orthorhombic phase of CuMnAs exists, see Ref. [7] for a phase diagram. Here we focus on tetragonal CuMnAs, which is stabilised by growth on suitably chosen substrates.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…On the experimental side, we note that orthorhombic phase of CuMnAs exists, see Ref. [7] for a phase diagram. Here we focus on tetragonal CuMnAs, which is stabilised by growth on suitably chosen substrates.…”
Section: Introductionmentioning
confidence: 75%
“…Both geometry and lattice constants were taken from literature (structure "II" in Ref. [20]) and the same values are used for all compositions and temper- In a separate work [29], various types of chemical disorder are discussed in detail while here, we investigate only prototypical and reasonable [7] Cu Mn defect with Cu impurities on Mn sublattices. Concentrations of this impurity are stated per formula unit.…”
Section: Formalism Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bulk form, CuMnAs was originally reported to have orthorhombic structure 9 while thin films grown on GaP or GaAs substrates 10 grow in a tetragonal phase. Recent studies of off-stoichiometric Cu 1+x Mn 1−x As compounds 11 have shown 12,13 that their crystal structure is rather sensitive to the composition. While the stoichiometric CuMnAs compounds crystallise in an orthorhombic structure (Pnma), few percent of copper excess at the expense of Mn turns the structure to a tetragonal one (P4/nmm).…”
mentioning
confidence: 99%
“…The two appendices focus on magnetic anisotropy of CuMnAs and its modelling and certain specialised aspects of micro- A sample of tetragonal CuMnAs was prepared by reaction of high purity copper, manganese and arsenic as previously reported. 13 Tetragonal P4/nmm structure was confirmed by powder x-ray diffraction at room temperature on Bruker D8 Advance diffractometer. 13 Composition analysis performed by energy-dispersive x-ray detector (EDX) suggests a slight prevalence of copper, the stoichiometry being 1.02(1):0.99(2):0.99 (2) for Cu:Mn:As; Néel temperature (T N ) is 507 K. From thus obtained polycrystal, a single-crystal grain was cleaved, oriented using x-ray diffraction and its orientation was further refined on an SEM stub holder using electron backscatter diffaction (EBSD).…”
mentioning
confidence: 99%